P Android-Based Monitoring and Control of Electricity Consumption: Android-Based Monitoring and Control of Electricity Consumption - Rahmat Azyad Samallo; Septi Andryana; Ratih Titi Komala Sari (Jurnal Mantik, 2020)
The purpose of this study is to create a system of "Monitoring and Control of Electricity Based on Android" where electricity is now an important part of people's daily lives and the community cannot be far from electricity because daily needs require electricity. There are bad habits of the people in using unnecessary and excessive electricity such as always turning on lights, fans, TVs and others when not at home so that electricity bills become expensive and uncontrolled. Monitoring and controlling electricity is one way to help the efficiency of the budget incurred due to unnecessary electricity usage. By using the Android Electric Monitoring and Control can be done remotely that can move the relay that is in the NodeMCU module ESP8266 so that electricity can be controlled with the system to be created and users no longer need to worry about electricity costs and forgetfulness to turn off the electricity that lights up because it can monitored via Android.